PENGEMBANGAN MODUL AJAR PADA MATERI WUDHU UNTUK MINAT BELAJAR SISWA DALAM MATA PELAJAR FIKIH DI MI AL FALAH KANIGORO PAGELARAN-MALANG - Suhartini; Nurhalimah, Evi (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2025)
The development of a teaching module on ablution material has innovation in helping children in stimulating the steps of ablution correctly. The purpose of describing the form of the teaching module on ablution material and the results of student learning interest when using the teaching module on ablution material in the subject of fiqh at MI Al-Falah Kanigoro Pagelaran-Malang. The research methodology used is Research and Development (RnD). Where, researchers focus on making products that have been designed with structured learning objectives. Researchers will validate the data, including product design indicators and the breadth of product material. The results and materials show that the product developed in the aspect of product design assessment, including image quality, layout, color combination, text and language, and visual power reaches a percentage of 90% of product design results. Meanwhile, the aspect of assessing the breadth of material, including KD material, ablution concepts, material presentation, language, student involvement reaches a percentage of 90% for the breadth of material. Researchers, using a posttest technique that reaches 66.25%. Meanwhile, the pretest achieved 85.10% using the teaching module in the learning process. The results of the development of student learning interest were 8.42 with statistical data hypothesis reaching 2.069. This shows that the ability of students' learning interest in using the teaching module on ablution material has increased significantly. The data concludes that the teaching module on ablution material is able to help students in practicing ablution independently with structured steps. Thus, educators can develop their ability to create creativity in creating teaching modules to support the learning process of elementary school students.